Formational Units in Sign Languages - Channon, Rachel (Sign Language Typology [SLT], 2011)
Sign languages and spoken languages have many fascinating differences, caused primarily by the reaction of the human mind to different modalities, but also by some important social differences. This book examines the effects of these and other differences on sign language phonology and phonetics using observation, experimentation and theory. Languages examined include Asian, Middle Eastern, European and American sign languages, and language situations include home signers and small village signers, children, gesturers, adult signers and non-native signers.